A study on public awareness towards Takaful business in Melaka / Muhamad Asyraf Rosli - Rosli, Muhamad Asyraf (Faculty of Business and Management, 2011)
Takaful or known as Islamic insurance is the way of bringing the social and also the economic advantages of conventional insurance protection by following the shariah compliance for the muslims and non-muslims people in this world. There world is undergoing rapid growth of Takaful but the development still have lots of barrier that need to be overcome by the Takaful operator. The facts that the way of Takaful operator handling the market can be said as very weak as the level of public awareness is still low. There are variables that being identified and successfully stressed in this paper. Later in the findings section, researcher will be able to provide recommendation for the future of Takaful industry. There are still long way to go and hardship for Takaful free from all barriers involved in this current situation. Therefore, it is become the responsibility of Takaful operator to educate and maintain the operation properly in order to become competence in industry.